INDONESIAN TERTIARY STUDENTS’ ATTITUDES TOWARDS THE USE OF LOCAL CULTURE VS TARGET CULTURE READING MATERIALS IN ENGLISH READING CLASS - Rodliyah, Rojab Siti; Imperiani, Ernie D.A; Amalia, Lulu Laela (Jurnal Pendidikan Bahasa dan Sastra, 2014)
This paper aims at portraying Indonesian tertiary students’ attitudes towards the use of local and target culture reading texts in English reading classes with regard to today’s role of English. It has been widely recognized that today’s role of English is as an international language (EIL) and as a lingua franca (ELF). Regarding this international role of English language, ideally teaching and learning English should be matched with appropriate pedagogical approach, in this case, EIL pedagogy approaches. In other words, teaching and learning EIL should be different from teaching and learning of any other second or foreign languages. Since Indonesia is categorized as an EFL country, it is interesting to find out whether this issue has an impact on ELT practices such as English reading class in this country. The subjects of the study are first year English Education Department students. The data were gained by delivering Likert scale questionnaire to the students on their attitude towards the reading materials given to them in one semester. In addition to this, an interview was conducted to verify the data and gain further information. The findings revealed that in general they show positive attitude to both local culture and target culture reading materials, with the majority of them prefer reading target culture reading materials. Furthermore, a considerable number of the students also acknowledge the importance of the use international culture along with English language teaching.